Perancangan Aplikasi E-Voting Berbasis Sidik Jari - Masnur Masnur; Syahirun Alam; Muhammad Zainal; Jaya Mahendra (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Fingerprint image recognition in computer applications is still rarely done, as in SMK Negeri 7 Pinrang which still elects student council presidents manually using paper media. The purpose of this study is to use fingerprint devices as a tool to obtain fingerprint data for students who will vote quickly and to reduce fraud that occurs in the election process. The problems that are often found in manual/traditional elections, fraud often occurs and require a large amount of money so that a new method is needed to solve this problem, namely by using a digital voting system or e-voting. This research is experimental in nature, where this type of research is direct field data collection which starts from directly observing conditions in the field, conducting interviews, collecting data, then processing it. The results of the tests carried out in this application have a 100% correct system success rate, system testing uses the Black Box Test and White Box Test and the system runs as expected in accordance with the design that has been made. So that the form of fraud in the process of selecting the student council chairman is no longer found